Polydopamine nanosheet, polydopamine-polyester composite material as well as preparation method and application of polydopamine nanosheet and polydopamine-polyester composite material
Large-sized polydopamine nanosheets were prepared through self-assembly and esterification reactions to form high-performance polydopamine-polyester composite materials, solving the problems of small size and low barrier properties of nanosheets in the prior art, and realizing polyester composite The materials have improved high barrier and mechanical properties, which are suitable for high-end market demand.
Patent Information
- Application Number
- CN202411304055.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2024-12-17
AI Technical Summary
The polydopamine nanosheets prepared in the prior art are small in size, and the coating composite method is difficult to improve the barrier performance of the polyester composite material, and cannot meet the requirements of the high-end market for high-barrier polyester composite materials.
Large-sized polydopamine nanosheets were prepared by dissolving organic matter of self-assembly characteristic molecules and polymerizing aqueous dopamine under alkaline conditions, and esterified with diol and dibasic acid to form high barrier properties Polydopamine-polyester composite material.
The average size of the prepared polydopamine nanosheets can reach 3 microns. The barrier properties and mechanical properties of the polydopamine-polyester composite materials have significantly improved, and have excellent biocompatibility. They are suitable for packaging and biomedical fields.
Smart Images

Figure CN119143989A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of nanomaterials, and in particular to a polydopamine nanosheet, a polydopamine-polyester composite material, and a preparation method and application thereof. Background Art
[0002] Dopamine (DA), also known as 3,4-dihydroxyamphetamine, is a neurotransmitter that exists in large quantities in the brain. It contains many functional groups and has a special chemical structure. DA can be polymerized under alkaline aerobic conditions at room temperature to obtain polydopamine (PDA). PDA has excellent physical and chemical properties and is a new type of material with wide applicability. It is widely used in the fields of material modification, drug loading, catalytic degradation, adsorption and corrosion protection.
[0003] Since PDA has strong adhesion, it can form a PDA layer by compounding with the surface of almost all inorganic or organic materials to modify the surface of the material, so it has received extensive attention and research. For example, PDA balls are used in drug delivery, heavy metal adsorption and degradation, catalysis, photothermal therapy, etc. PDA also has excellent biological activity and adhesion, so PDA capsules are widely used in drug carriers, bionics, biosensors and other fields. Sheet-like two-dimensional materials have a large specific surface area, which can extend the medium penetration path in the polymer matrix and greatly improve the barrier properties of the polymer. PDA, as a two-dimensional material modifier, has also shown excellent performance in the barrier field. However, the currently prepared PDA nanosheets are small in size, and the coating composite method used in the existing technology has limited improvement in the barrier properties of polyester composites, making it difficult to meet the requirements of the existing high-end market for high-barrier polyester composites. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention provides a polydopamine nanosheet, a polydopamine-polyester composite material, and a preparation method and application thereof. The prepared polydopamine nanosheet has a larger size, and the polydopamine-polyester composite material has excellent barrier properties.
[0005] The present invention provides a method for preparing polydopamine nanosheets, comprising the following steps: S1. Organic matter with self-assembly molecular properties is dissolved in a solvent to form a dispersion; S2, adding deionized water to the dispersion liquid in step S1, and continuously stirring until the organic matter self-assembles to form a template, thereby obtaining a template liquid; S3, adding an aqueous solution of dopamine to the template liquid in step S2 to form a dopamine mixed solution, adding a pH regulator to the dopamine mixed solution, adjusting the pH value of the dopamine mixed solution to be alkaline, and continuously stirring until the polymerization reaction is completed to obtain a mixed solution containing polydopamine nanosheets; S4. The mixed solution in step S3 is post-treated to obtain polydopamine nanosheets.
[0006] The preparation method of polydopamine nanosheets provided by the present invention utilizes organic molecules with self-assembly characteristics to first form a template through self-assembly in a solution, and then polymerizes dopamine on the template to form polydopamine nanosheets with larger sizes, thereby solving the problem of small sizes of two-dimensional polydopamine nanosheets prepared in the prior art.
[0007] In a possible embodiment, the organic matter having self-assembly property molecules in step S1 includes one or more of cholesterol, phospholipids, amphiphilic fatty acids, amphiphilic fatty amines, sodium dodecyl sulfate, 1-octanol, cocamidopropyl betaine and benzalkonium chloride.
[0008] Furthermore, the phospholipid is one or more of phosphatidylcholine, phosphatidylethanolamine, phosphatidylserine, phosphatidylinositol, phosphatidylglycerol and glycerophosphatidic acid.
[0009] Furthermore, the amphiphilic fatty acid is an alkyl acid having 8-22 carbon atoms in the carbon chain.
[0010] Furthermore, the amphiphilic fatty amine is an alkylamine having 8 to 22 carbon atoms in the carbon chain.
[0011] In a possible implementation, the concentration of the organic matter having self-assembly molecules in the dispersion in step S1 is 0.1-100 mg / mL.
[0012] In a possible implementation, the solvent in step S1 includes one or more of methanol, ethanol, acetone, N,N-dimethylformamide, acetonitrile, tetrahydrofuran and dimethyl sulfoxide.
[0013] In a possible implementation, the volume ratio of the solvent in step S1 to the deionized water in step S2 is 1:(1-500), preferably 1:(1-300).
[0014] In a possible implementation manner, the stirring time in step S2 is 0.1-2 h, preferably 0.1-1 h.
[0015] In a possible implementation, the concentration of dopamine in the aqueous solution of dopamine in step S3 is 0.1-200 mg / mL.
[0016] In a possible embodiment, the molar ratio of dopamine in step S3 to the organic matter having self-assembly molecules in step S1 is (1-50): 1, preferably (2-40): 1. By controlling the usage ratio of dopamine to the organic matter having self-assembly molecules, the size of the prepared polydopamine can be regulated.
[0017] In a possible implementation, the pH regulator in step S3 includes sodium hydroxide solution or ammonia water. The dopamine solution is adjusted to be alkaline by using sodium hydroxide solution or ammonia water, which is beneficial to promote the polymerization reaction and accelerate the polymerization reaction speed.
[0018] In a possible implementation, the pH value of the polydopamine mixed solution in step S3 is 7.5-8.5. By adjusting the pH value of the polydopamine mixed solution, the size of the obtained polydopamine nanosheets can be adjusted.
[0019] In a possible implementation, the temperature of the polymerization reaction in step S3 is 20-80° C., preferably 25-60° C. By controlling the temperature of the polymerization reaction, the polymerization reaction is promoted to proceed quickly.
[0020] In a possible embodiment, the polymerization reaction time in step S3 is 12-48 h. By controlling the polymerization reaction time, the size of the prepared polydopamine nanosheets can be controlled. In one possible embodiment, the post-treatment includes one or more treatment steps of centrifugation, washing and freeze-drying.
[0021] Furthermore, the centrifugal speed is 5000-20000 rpm and the time is 5-60 min. By controlling the centrifugal speed and centrifugal time, unnecessary damage to the polydopamine nanosheets can be avoided.
[0022] More preferably, the centrifugal speed is 6000-15000 rpm and the time is 5-45 min.
[0023] The present invention also provides polydopamine nanosheets prepared according to the above-mentioned method for preparing polydopamine nanosheets, wherein the size of the polydopamine nanosheets is 0.1-10 μm and the thickness is 0.7-30 nm.
[0024] The present invention also provides a method for preparing a polydopamine-polyester composite material, comprising the following steps: D1, adding the polydopamine nanosheets into diol, stirring and dispersing them evenly to form a dispersed solution; D2. After adding the dibasic acid and / or its esterified product into the dispersed solution in step D1, esterification and / or transesterification and polycondensation reaction are carried out to synthesize the polydopamine-polyester composite material.
[0025] The preparation method of the polydopamine-polyester composite material provided by the present invention comprises the following steps: adding large-sized dopamine nanosheets into diol to make the polydopamine more uniformly dispersed, and then reacting with polyester to form a polydopamine-polyester composite material with high barrier performance. Since the composite material is formed by the reaction of polydopamine and polyester, the composite material belongs to a strong-interface high-performance organic-organic nanocomposite material, which overcomes the problem of poor organic-inorganic interface in the prior art, has better interface compatibility, and can greatly improve the barrier and mechanical properties of the polydopamine-polyester nanocomposite material.
[0026] In a possible implementation, the diol in step D1 includes aliphatic diol and / or cyclic diol. By selecting a suitable diol solvent, the polydopamine nanosheets can be dispersed more evenly.
[0027] Furthermore, the aliphatic diol includes one or more of ethylene glycol, propylene glycol, butylene glycol, pentylene glycol, hexylene glycol, octanediol, neopentyl glycol and isosorbide.
[0028] Furthermore, the cyclic diol includes one or more of tricyclodecanediol, tricyclodecane dimethanol and tetracyclic diol.
[0029] In a possible implementation, the stirring speed of the stirring and dispersing in step D1 is 1000-20000 rpm and the time is 0.1-72 h. By controlling the stirring speed and stirring time, the polydopamine nanosheets can be dispersed more evenly.
[0030] In a possible implementation manner, the content of the polydopamine nanosheets in the dispersed solution in step D1 is 0.01-10 wt %. By controlling the concentration of the polydopamine nanosheets, the barrier properties of the polydopamine-polyester composite material can be further improved.
[0031] In a possible implementation, the polydopamine nanosheets in step D1 are polydopamine nanosheet powder or polydopamine nanosheet slurry.
[0032] In a possible implementation, the dibasic acid in the dibasic acid and / or its ester in step D2 includes one or more of terephthalic acid, terephthalic acid esters, furandicarboxylic acid, furandicarboxylic acid esters, thiophenedicarboxylic acid and thiophenedicarboxylic acid esters.
[0033] In one possible implementation, the molar ratio of the dibasic acid and / or its ester in step D2 to the diol in step D1 is 1:(1.2-3).
[0034] The present invention also provides a polydopamine-polyester composite material prepared by the preparation method of the polydopamine-polyester composite material.
[0035] The present invention also provides application of the polydopamine-polyester composite material in the packaging field and the biomedical field.
[0036] Based on the common knowledge in this field, the above-mentioned implementation modes can be combined arbitrarily.
[0037] The reagents and raw materials used in the present invention are commercially available.
[0038] The positive and progressive effects of the present invention are: The preparation method of the polydopamine nanosheet provided by the present invention can not only prepare large-sized polydopamine nanosheets, the average size of the prepared polydopamine nanosheets can reach 3 microns, and has the advantages of simple preparation process, low cost, and easy large-scale production. The preparation method of the polydopamine-polyester composite material provided by the present invention synthesizes the polydopamine-polyester composite material by an in-situ polymerization method, which is a strong interface high-performance organic-organic nanocomposite material. The strength, toughness, and barrier properties of the prepared polydopamine-polyester composite material are greatly improved compared with similar products, and it has excellent biocompatibility, and has great application potential in the packaging field and biomedical field, and the preparation method of the polydopamine-polyester composite material is highly operable and popularizable. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 This is a photo of the polydopamine nanosheets prepared in Example 1 after freeze-drying.
[0040] Figure 2 This is a physical picture of the polydopamine nanosheet slurry prepared in Example 2.
[0041] Figure 3 This is the SEM image of the polydopamine nanosheets prepared in Example 3.
[0042] Figure 4 This is an AFM image of the polydopamine nanosheets prepared in Example 4.
[0043] Figure 5 This is the TEM image of the polydopamine nanosheets prepared in Example 5.
[0044] Figure 6 This is the size distribution diagram of the polydopamine nanosheets prepared in Example 6.
[0045] Figure 7 This is the infrared spectrum of the polydopamine nanosheets prepared in Example 7.
[0046] Figure 8 This is a test chart of the visible light transmittance of the polydopamine-polyethylene terephthalate composite material prepared in Example 8.
[0047] Fig. 9 This is a diagram showing the barrier performance test results of the polydopamine-ethylene furandicarboxylate composite material prepared in Example 9.
[0048] Fig.10 This is a cross-sectional SEM image of the polydopamine-polyethylene terephthalate composite material prepared in Example 10.
[0049] Fig.11 This is a mechanical property curve of the polydopamine-butylene furandicarboxylate composite material prepared in Example 11. DETAILED DESCRIPTION
[0050] In order to make the above-mentioned purposes, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below. It should be noted that the following embodiments are only used to illustrate the implementation method and typical parameters of the present invention, and are not used to limit the parameter range described in the present invention. Reasonable changes derived therefrom are still within the scope of protection of the claims of the present invention.
[0051] It should be noted that the endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed in this article.
[0052] Unless otherwise defined, all terms, symbols and other scientific terms used herein are intended to have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. In some cases, terms with conventionally understood meanings are defined herein for the purpose of clarification or ease of reference, and such definitions herein should not be construed as indicating significant differences from conventional understandings in the art. The technical methods described or cited herein are generally well understood by those skilled in the art and are adopted by conventional methods. Unless otherwise stated, the use of commercially available kits, reagents and instruments is carried out in accordance with the protocols and parameters given by the manufacturer.
[0053] The test and analysis methods used in the following embodiments are as follows: Infrared spectroscopy analysis: Thermo Scientific Nicolet 6700 was used to perform Fourier transform attenuated total reflection infrared spectroscopy analysis on the samples of the embodiment, and the test range was 4000-400 cm.
[0054] Tensile strength: According to ASTM D638, the tensile test was carried out at 25°C and a tensile rate of 10 mm / min using a Roell Z020 universal material testing machine from Zwick, Germany. Five specimens were tested for each sample, and the average value was taken as the test result.
[0055] Transmission electron microscopy (TEM) test: Using a JEM2100 transmission electron microscope, the sample was dispersed in ethanol, dropped onto the prepared copper grid, and dried under an infrared lamp for testing.
[0056] Scanning electron microscope (SEM) test: German ZEISS, model EVO18 scanning electron microscope was used. Before the test, the sample powder was evenly spread on the silicon wafer, and then the silicon wafer carrying the sample was glued to the sample stage with conductive glue. The test voltage was 10-20 KV and the working distance was 10 mm.
[0057] Scanning probe microscope (AFM) test: A scanning probe microscope (Dimension ICON, Bruker, Germany) was used. The sample was dispersed in ethanol, dropped on the prepared silicon wafer, and dried under an infrared lamp. The test was performed in surface tapping mode with a scanning speed of 1.9 mV / s.
[0058] Gas barrier performance test: Labthink VAC-V2 was used to measure the gas barrier performance at a temperature of 23°C and a humidity of 50% RH. The sample size was Φ = 97 mm and the penetration area was 38.5 cm 2 .
[0059] Example 1
[0060] This embodiment provides a two-dimensional polydopamine nanosheet powder and a polydopamine-polyethylene terephthalate (PET) nanocomposite material, which are prepared by the following method: Octadecylamine was dissolved in ethanol to prepare a 1 mg / mL solution, and then deionized water was added, wherein the volume ratio of ethanol to water was 1:5. After stirring at room temperature for 10 min, 0.5 mg / mL dopamine solution was slowly added to make the molar ratio of dopamine to octadecylamine 2:1, and the pH of the system was adjusted to 7.5 with NaOH aqueous solution. The reaction was terminated after stirring at room temperature for 48 h. The mixed solution was then centrifuged at 20,000 rpm for 20 min, and then washed with a mixed solvent of ethanol and water, and then the washed product was freeze-dried to obtain a two-dimensional PDA nanosheet powder.
[0061] A certain amount of two-dimensional PDA nanosheet powder was weighed and dispersed in ethylene glycol at a mass fraction of 0.01 wt%, and then stirred at 1000 rpm for 72 h to form a dispersed solution. Subsequently, terephthalic acid and the dispersed solution were added to the reactor at a molar ratio of 1:3, and antimony trioxide with a mass fraction of 1 wt‰ was added as an esterification catalyst and polycondensation catalyst. The esterification temperature was set at 240 ℃, and the reaction was carried out under nitrogen protection. When the esterification rate reached 90% of the theoretical value, triphenyl phosphate with a mass fraction of 1 wt‰ was added, and the polycondensation temperature was set at 285 ℃. After low vacuum pre-polycondensation (vacuum degree greater than 200 Pa) for 1 h, high vacuum polycondensation (vacuum degree less than 20 Pa) was carried out for 4 h. After the polycondensation was completed, the PDA / polyethylene terephthalate (PET) nanocomposite material was obtained by discharging.
[0062] The appearance of the PDA nanosheets obtained in this example is as follows Figure 1 As shown in the figure, it can be seen that the PDA nanosheets obtained after freeze-drying have typical powder-like properties, which is conducive to the uniform dispersion of the nanosheets in the next step of in-situ polymerization.
[0063] Example 2
[0064] This embodiment provides a two-dimensional polydopamine nanosheet slurry and a polydopamine-polyethylene terephthalate (PET) nanocomposite material, which are prepared by the following method: Octadecanyl acid was dissolved in methanol to prepare a 1.5 mg / mL solution, and then deionized water was added, wherein the volume ratio of ethanol to water was 1:8. After stirring at room temperature for 20 min, 1 mg / mL dopamine solution was slowly added to make the molar ratio of dopamine to octadecanoic acid 3:1, and the pH of the system was adjusted to 8.0 with NaOH solution. The reaction was terminated after stirring at 30 °C for 24 h. The mixed solution was then centrifuged at 18000 rpm for 15 min, and then washed with a mixed solvent of methanol and water, and then the washed product was filtered to obtain a two-dimensional PDA nanosheet slurry.
[0065] A certain amount of two-dimensional PDA nanosheet slurry was weighed and dispersed in ethylene glycol at a mass fraction of 0.05 wt%, and then stirred at a speed of 1500 rpm for 60 h to form a dispersed solution. Subsequently, methyl terephthalate and the dispersed solution were added to the reactor at a molar ratio of 1:2.5, and 1.1 wt‰ of tetrabutyl titanate was added as an esterification catalyst and polycondensation catalyst. The transesterification temperature was set to 235 ℃, and the reaction was carried out under nitrogen protection. When the esterification rate reached 90% of the theoretical value, 1 wt‰ of triphenyl phosphate, a stabilizer, was added, and the polycondensation temperature was set to 285 ℃. After low vacuum pre-polycondensation (vacuum degree greater than 200 Pa) for 1 h, high vacuum polycondensation (vacuum degree less than 20 Pa) was carried out for 4 h. After the polycondensation was completed, the PDA / PET nanocomposite material was obtained by discharging.
[0066] The appearance of the PDA nanosheet slurry obtained in this example is as follows Figure 2 As shown in the figure, it can be seen that the obtained PDA nanosheet solution is black and has a high viscosity.
[0067] Example 3
[0068] This embodiment provides a two-dimensional polydopamine nanosheet slurry and a polydopamine-polyethylene terephthalate (PET) nanocomposite material, which are prepared by the following method: Phosphatidylcholine was dissolved in ethanol to prepare a 2 mg / mL solution, and then deionized water was added, wherein the volume ratio of ethanol to water was 1:10. After stirring at room temperature for 30 min, 1.5 mg / mL dopamine solution was slowly added to make the molar ratio of dopamine to phosphatidylcholine 3:1, and the pH of the system was adjusted to 8.5 with NaOH solution. The reaction was terminated after stirring at 40°C for 24 hours. The mixed solution was then centrifuged at 15,000 rpm for 10 min, and then washed with a mixed solvent of ethanol and water, and then the washed product was filtered to obtain a two-dimensional PDA nanosheet slurry.
[0069] A certain amount of two-dimensional PDA nanosheets was weighed and dispersed in ethylene glycol at a mass fraction of 0.1 wt%, and then stirred at a speed of 2000 rpm for 48 h to form a dispersed solution. Subsequently, terephthalic acid and the dispersed solution were added to the reactor at a molar ratio of 1:2, and anhydrous zinc acetate with a mass fraction of 1 wt‰ was added as an esterification catalyst. The esterification temperature was set to 240 ℃, and the reaction was carried out under nitrogen protection. When the esterification rate reached 90% of the theoretical value, 1 wt‰ of triphenyl phosphate stabilizer and 1 wt‰ of antimony trioxide polycondensation catalyst were added, and the polycondensation temperature was set to 285 ℃. After low vacuum pre-polycondensation (vacuum degree greater than 200 Pa) for 1 h, high vacuum polycondensation (vacuum degree less than 20 Pa) was carried out for 4 h. After the polycondensation was completed, the PDA / PET nanocomposite material was obtained by discharging.
[0070] The SEM image of the PDA nanosheets obtained in this example is as follows: Figure 3 As shown in the figure, it can be proved that the synthesized PDA nanosheets do have a typical two-dimensional sheet morphology, and their wrinkled morphology indicates that the nanosheets have a thin thickness, marking the successful synthesis of PDA nanosheets.
[0071] Example 4
[0072] This embodiment provides a two-dimensional polydopamine nanosheet powder and a polydopamine-polyethylene terephthalate (PET) nanocomposite material, which are prepared by the following method: Phosphatidylethanolamine was dissolved in ethanol to prepare a 2.5 mg / mL solution, and then deionized water was added, wherein the volume ratio of ethanol to water was 1:15. After stirring at room temperature for 45 min, 2 mg / mL dopamine solution was slowly added to make the molar ratio of dopamine to phosphatidylethanolamine 4:1, and the pH of the system was adjusted to 8 with NaOH solution. The reaction was terminated after stirring at 50 °C for 18 h. The mixed solution was then centrifuged at 15,000 rpm for 7 min, and then washed with a mixed solvent of ethanol and water, and then the washed product was freeze-dried to obtain a two-dimensional PDA nanosheet powder.
[0073] A certain amount of two-dimensional PDA nanosheets was weighed and dispersed in ethylene glycol at a mass fraction of 0.2 wt%, and then stirred at 2500 rpm for 72 h to form a dispersed solution. Subsequently, furan dicarboxylic acid and the dispersed solution were added to the reactor at a molar ratio of 1:1.8, and antimony trioxide with a mass fraction of 1 wt‰ was added as an esterification catalyst and polycondensation catalyst. The esterification temperature was set to 220 ℃, and the reaction was carried out under nitrogen protection. When the esterification rate reached 90% of the theoretical value, triphenyl phosphate with a mass fraction of 1 wt‰ was added, and the polycondensation temperature was set to 240 ℃. After low vacuum pre-polycondensation (vacuum degree greater than 200 Pa) for 1 h, high vacuum polycondensation (vacuum degree less than 20 Pa) was carried out for 4 h. After the polycondensation was completed, the PDA / polyethylene terephthalate (PEF) nanocomposite material was obtained by discharging.
[0074] The AFM image of the PDA nanosheets obtained in this example is as follows: Figure 4 As shown in the figure, it can be seen that the PDA nanosheets have a large lateral size of about 3-5 μm and a thin thickness of about 2 nm.
[0075] Example 5
[0076] This embodiment provides a two-dimensional polydopamine nanosheet powder and a polydopamine-polybutylene terephthalate (PBT) nanocomposite material, which are prepared by the following method: Phosphatidylserine was dissolved in N,N-dimethylformamide to prepare a 3 mg / mL solution, and then deionized water was added, wherein the volume ratio of ethanol to water was 1:20. After stirring at room temperature for 60 min, 4 mg / mL dopamine solution was slowly added to make the molar ratio of dopamine to phosphatidylserine 6:1, and the pH of the system was adjusted to 8 with NaOH solution. The reaction was terminated after stirring at 60°C for 12 h. The mixed solution was then centrifuged at 10,000 rpm for 20 min, and then washed with a mixed solvent of N,N-dimethylformamide / water, and then the washed product was freeze-dried to obtain a two-dimensional PDA nanosheet powder.
[0077] A certain amount of two-dimensional PDA nanosheet powder was weighed and dispersed in butanediol at a mass fraction of 0.4 wt%, and then stirred at a speed of 5000 rpm for 48 h to form a dispersed solution. Subsequently, terephthalic acid and the dispersed solution were added to the reactor at a molar ratio of 1:1.6, and 1 wt‰ of tetrabutyl titanate was added as an esterification catalyst and polycondensation catalyst. The esterification temperature was set to 210 ℃, and the reaction was carried out under nitrogen protection. When the esterification rate reached 90% of the theoretical value, 1 wt‰ of triphenyl phosphate, a stabilizer, was added, and the polycondensation temperature was set to 250 ℃. After low vacuum pre-polycondensation (vacuum degree greater than 200 Pa) for 1 h, high vacuum polycondensation (vacuum degree less than 20 Pa) was carried out for 4 h. After the polycondensation was completed, the PDA / polybutylene terephthalate (PBT) nanocomposite material was obtained by discharging.
[0078] The TEM image of the PDA nanosheet obtained in this example is as follows: Figure 5 As shown in the figure, it can be seen that the synthesized PDA nanosheets have ultra-thin thickness and complete surface structure.
[0079] Example 6
[0080] This embodiment provides a two-dimensional polydopamine nanosheet powder and a polydopamine-polybutylene terephthalate (PPT) nanocomposite material, which are prepared by the following method: Dissolve heptadecylamine in ethanol to prepare a 4 mg / mL solution, then add deionized water, where the volume ratio of ethanol to water is 1:35, stir at room temperature for 45 min, slowly add 5 mg / mL dopamine solution, so that the molar ratio of dopamine to heptadecylamine is 10:1, and adjust the pH of the system to 8.5 with NaOH solution, and stir at 40 ° C for 24 h before the reaction ends. Then centrifuge the mixed solution at 13000 rpm for 15 min, wash with a mixed solvent of ethanol / water, and then freeze-dry the washed product to obtain a two-dimensional PDA nanosheet powder.
[0081] A certain amount of two-dimensional PDA nanosheet powder was weighed and dispersed in propylene glycol at a mass fraction of 0.6 wt%, and then stirred at 8000 rpm for 48 h to form a dispersed solution. Subsequently, terephthalic acid and the dispersed solution were added to the reactor at a molar ratio of 1:1.8, and antimony trioxide with a mass fraction of 1 wt‰ was added as an esterification catalyst and polycondensation catalyst. The esterification temperature was set at 250 ℃, and the reaction was carried out under nitrogen protection. When the esterification rate reached 90% of the theoretical value, triphenyl phosphate with a mass fraction of 1 wt‰ was added, and the polycondensation temperature was set at 280 ℃. After low vacuum pre-polycondensation (vacuum degree greater than 200 Pa) for 1 h, high vacuum polycondensation (vacuum degree less than 20 Pa) was carried out for 4 h. After the polycondensation was completed, the PDA / polybutylene terephthalate (PPT) nanocomposite material was obtained by discharging.
[0082] The size distribution of the PDA nanosheets obtained in this example is as follows Figure 6 As shown in the figure, it can be seen that the PDA nanosheets have ultra-high lateral dimensions, with a maximum of 7 μm, and the average size of the synthesized nanosheets is 3±0.21 μm.
[0083] Example 7
[0084] This embodiment provides a two-dimensional polydopamine nanosheet slurry and a polydopamine-polyisosorbide terephthalate-ethylene glycol nanocomposite material, which are prepared by the following method: Hexadecylamine was dissolved in ethanol to prepare a 5 mg / mL solution, and then deionized water was added, wherein the volume ratio of ethanol to water was 1:40, and after stirring at room temperature for 30 min, 8 mg / mL dopamine solution was slowly added to make the molar ratio of dopamine to heptadecylamine 15:1, and the pH of the system was adjusted to 8.0 with NaOH solution, and the reaction was terminated after stirring at 35°C for 36 h. The mixed solution was then centrifuged at 12000 rpm for 20 min, and then washed with a mixed solvent of ethanol / water, and the washed product was then stored in the form of slurry.
[0085] A certain amount of two-dimensional PDA slurry was weighed and dispersed in a mixture of isosorbide and ethylene glycol (molar ratio of isosorbide and ethylene glycol 1:1) at a mass fraction of 0.8 wt%, and then stirred at a speed of 10000 rpm for 54 h to form a dispersed solution. Subsequently, dimethyl terephthalate and the dispersed solution were added to the reactor at a molar ratio of 1:2.1, and antimony trioxide with a mass fraction of 1 wt‰ was added as an esterification catalyst and polycondensation catalyst. The esterification temperature was set at 250 ℃, and the reaction was carried out under nitrogen protection. When the esterification rate reached 90% of the theoretical value, triphenyl phosphate with a mass fraction of 1 wt‰ was added, and the polycondensation temperature was set at 280 ℃. After low vacuum pre-polycondensation (vacuum degree greater than 200 Pa) for 1 h, high vacuum polycondensation (vacuum degree less than 20 Pa) was carried out for 4 h. After the polycondensation was completed, the PDA / polyisosorbide-ethylene terephthalate nanocomposite material was obtained by discharging.
[0086] The infrared spectrum of the PDA nanosheets obtained in this example is as follows Figure 7 As shown in the figure, it can be seen that the PDA nanosheets still retain the chemical structure of polydopamine and contain abundant hydroxyl and amino groups, which are conducive to forming intermolecular hydrogen bonds with polyester and increasing the interfacial force between the nanosheets and the polyester material.
[0087] Example 8
[0088] This embodiment provides a two-dimensional polydopamine nanosheet slurry and a polydopamine-polyethylene terephthalate (PET) nanocomposite material, which are prepared by the following method: Hexadecanoic acid was dissolved in ethanol to prepare a 10 mg / mL solution, and then deionized water was added, wherein the volume ratio of ethanol to water was 1:50, and after stirring at room temperature for 35 min, a 10 mg / mL dopamine solution was slowly added to make the molar ratio of dopamine to heptadecylamine 20:1, and the pH of the system was adjusted to 8.0 with a NaOH solution, and the reaction was terminated after stirring at 25°C for 12 h. The mixed solution was then centrifuged at 15,000 rpm for 25 min, and then washed with a mixed solvent of ethanol and water, and the washed product was then stored in the form of slurry.
[0089] A certain amount of two-dimensional PDA slurry was weighed to make it 1.0 wt % and dispersed in ethylene glycol, and then stirred at 15000 rpm for 48 h. Then, terephthalic acid and dispersion were added into the reactor at a molar ratio of 1 / 2.5, and antimony trioxide with a mass fraction of 1 wt‰ was added as an esterification catalyst and polycondensation catalyst. The esterification temperature was set to 255 ℃, and the reaction was carried out under nitrogen protection. When the esterification rate reached 90% of the theoretical value, triphenyl phosphate with a mass fraction of 1 wt‰ was added, and the polycondensation temperature was set to 290 ℃. After low vacuum pre-polycondensation (vacuum degree greater than 200 Pa) for 1 h, high vacuum polycondensation (vacuum degree less than 20 Pa) was carried out for 4 h. After the polycondensation was completed, the PDA / PET nanocomposite material was obtained by discharging.
[0090] The visible light transmittance of the PDA / PET nanocomposite material obtained in this example is as follows: Figure 8 As shown in the figure, it can be seen that the prepared nanocomposite material has good ultraviolet shielding performance and can completely shield ultraviolet rays with a wavelength below 320 nm. It also has good transmittance in the visible light region.
[0091] Example 9
[0092] This embodiment provides a two-dimensional polydopamine nanosheet slurry and a polydopamine-polyethylene terephthalate (PET) nanocomposite material, which are prepared by the following method: Tetradecanoic acid was dissolved in ethanol to prepare a 15 mg / mL solution, and then deionized water was added, wherein the volume ratio of ethanol to water was 1:80, and after stirring at room temperature for 30 min, a 20 mg / mL dopamine solution was slowly added to make the molar ratio of dopamine to tetradecanoic acid 30:1, and the pH of the system was adjusted to 8.0 with a NaOH solution, and the reaction was terminated after stirring at 35°C for 18 h. The mixed solution was then centrifuged at 12,000 rpm for 30 min, and then washed with a mixed solvent of ethanol and water, and the washed product was then stored in the form of slurry.
[0093] A certain amount of two-dimensional PDA slurry was weighed and dispersed in ethylene glycol at a mass fraction of 1.2 wt%, and then stirred at 20000 rpm for 24 h to form a dispersed solution. Subsequently, dimethyl furandicarboxylate and the dispersed solution were added to the reactor at a molar ratio of 1:2.1, and zinc acetate with a mass fraction of 1 wt‰ was added as an esterification catalyst. The esterification temperature was set to 220 ℃, and the reaction was carried out under nitrogen protection. When the esterification rate reached 90% of the theoretical value, 1 wt‰ stabilizer triphenyl phosphate and 1.2 wt‰ polycondensation catalyst antimony trioxide were added, and the polycondensation temperature was set to 240 ℃. After low vacuum pre-polycondensation (vacuum degree greater than 200 Pa) for 1 h, high vacuum polycondensation (vacuum degree less than 20 Pa) was carried out for 4 h. After the polycondensation was completed, the PDA / PEF nanocomposite material was obtained by discharging.
[0094] The barrier properties of the PDA / PEF nanocomposite obtained in this example are as follows: Fig. 9 As shown in the figure, it can be seen that compared with PEF polyester, the oxygen barrier performance of PDA / PEF nanocomposite materials is improved by 4.9 times. This is because the introduction of PDA nanosheets constructs a nanostructure inside the composite material, which extends the gas diffusion path and thus improves the barrier performance.
[0095] Example 10
[0096] This embodiment provides a two-dimensional polydopamine nanosheet slurry and a polydopamine-polyethylene terephthalate (PET) nanocomposite material, which are prepared by the following method: Dodecylamine was dissolved in ethanol to prepare a 20 mg / mL solution, and then deionized water was added, wherein the volume ratio of ethanol to water was 1:100, and after stirring at room temperature for 40 min, a 40 mg / mL dopamine solution was slowly added to make the molar ratio of dopamine to dodecylamine 40:1, and the pH of the system was adjusted to 8.0 with a NaOH solution, and the reaction was terminated after stirring at 25 °C for 24 h. The mixed solution was then centrifuged at 13,000 rpm for 25 min, and then washed with a mixed solvent of ethanol and water, and the washed product was then stored in the form of slurry.
[0097] A certain amount of two-dimensional PDA slurry was weighed and dispersed in ethylene glycol at a mass fraction of 2 wt%, and then stirred at a speed of 17000 rpm for 12 h to form a dispersed solution. Subsequently, dimethyl terephthalate and the dispersed solution were added to the reactor at a molar ratio of 1:1.8, and zinc acetate with a mass fraction of 1 wt‰ was added as an esterification catalyst. The esterification temperature was set to 240 ℃, and the reaction was carried out under nitrogen protection. When the esterification rate reached 90% of the theoretical value, 1 wt‰ of triphenyl phosphate as a stabilizer and 1.2 wt‰ of antimony trioxide as a polycondensation catalyst were added, and the polycondensation temperature was set to 275 ℃. After low vacuum pre-polycondensation (vacuum degree greater than 200 Pa) for 1 h, high vacuum polycondensation (vacuum degree less than 20 Pa) was carried out for 4 h. After the polycondensation was completed, the PDA / PET nanocomposite material was obtained by discharging.
[0098] The SEM image of the cross section of the PDA / PET nanocomposite material obtained in this example is as follows: Fig.10 As shown in the figure, it can be seen that due to the presence of a large number of hydroxyl and amino groups on the surface of PDA nanosheets, PDA nanosheets have good compatibility in the PET polyester matrix, and PDA is evenly dispersed inside the composite material without agglomeration.
[0099] Embodiment 11
[0100] This embodiment provides a two-dimensional polydopamine nanosheet powder and a polydopamine-ethylene furandicarboxylate (PEF) nanocomposite material, which is prepared by the following method: The decanylamine was dissolved in ethanol to prepare a 30 mg / mL solution, and then deionized water was added, wherein the volume ratio of ethanol to water was 1:150, and after stirring at room temperature for 50 min, 80 mg / mL of dopamine solution was slowly added to make the molar ratio of dopamine to decanylamine 60:1, and the pH of the system was adjusted to 8.5 with NaOH solution, and the reaction was terminated after stirring at 35°C for 20 h. The mixed solution was then centrifuged at 11000 rpm for 45 min, and then washed with a mixed solvent of ethanol and water, and the washed product was then stored in the form of slurry.
[0101] A certain amount of two-dimensional PDA slurry was weighed and dispersed in ethylene glycol at a mass fraction of 5 wt%, and then stirred at a speed of 15000 rpm for 15 h to form a dispersed solution. Subsequently, furandicarboxylic acid dimethyl ester and the dispersed solution were added into the reactor at a molar ratio of 1:1.6, and zinc acetate with a mass fraction of 1 wt‰ was added as an esterification catalyst. The esterification temperature was set to 220 ℃, and the reaction was carried out under nitrogen protection. When the esterification rate reached 90% of the theoretical value, 1 wt‰ of triphenyl phosphate as a stabilizer and 1.1 wt‰ of antimony trioxide as a polycondensation catalyst were added, and the polycondensation temperature was set to 240 ℃. After low vacuum pre-polycondensation (vacuum degree greater than 200 Pa) for 1 h, high vacuum polycondensation (vacuum degree less than 20 Pa) was carried out for 4 h. After the polycondensation was completed, the PDA / ethylene glycol furandicarboxylic acid (PEF) nanocomposite material was obtained by discharging.
[0102] The mechanical property curve of the PDA / PEF nanocomposite obtained in this example is as follows: Fig.11 As shown in the figure, it can be seen that the PDA / PEF nanocomposite has an ultra-high fracture strength of about 200 MPa. Since the nanonetwork constructed by the PDA nanosheets inside the PEF matrix effectively dissipates stress and deflects the crack direction, the PDA / PEF nanocomposite has excellent mechanical properties.
[0103] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing polydopamine nanosheets, characterized in that: The following steps are involved: S1. Organic matter with self-assembly molecular properties is dissolved in a solvent to form a dispersion; S2, adding deionized water to the dispersion liquid in step S1, and continuously stirring until the organic matter self-assembles to form a template, thereby obtaining a template liquid; S3, adding an aqueous solution of dopamine to the template liquid in step S2 to form a dopamine mixed solution, adding a pH regulator to the dopamine mixed solution, adjusting the pH value of the dopamine mixed solution to be alkaline, and continuously stirring until the polymerization reaction is completed to obtain a mixed solution containing polydopamine nanosheets; S4. The mixed solution in step S3 is post-treated to obtain polydopamine nanosheets.
2. The method for preparing polydopamine nanosheets according to claim 1, characterized in that: The organic matter having self-assembly property molecules in step S1 includes one or more of cholesterol, phospholipids, amphiphilic fatty acids, amphiphilic fatty amines, sodium dodecyl sulfate, 1-octanol, cocamidopropyl betaine and benzalkonium chloride; The concentration of the organic matter having self-assembly property molecules in the dispersion liquid of step S1 is 0.1-100 mg / mL; And / or, the solvent in step S1 includes one or more of methanol, ethanol, acetone, N,N-dimethylformamide, acetonitrile, tetrahydrofuran and dimethyl sulfoxide; And / or, the volume ratio of the solvent in step S1 to the deionized water in step S2 is 1:(1-500); And / or, the stirring time in step S2 is 0.1-2 h; And / or, the concentration of dopamine in the aqueous solution of dopamine in step S3 is 0.1-200 mg / mL; And / or, the molar ratio of dopamine in step S3 to the organic substance having self-assembly molecule in step S1 is (1-50):1; And / or, the pH regulator in step S3 includes aqueous sodium hydroxide solution or aqueous ammonia; And / or, the pH value of the polydopamine mixed solution in step S3 is 7.5-8.5; And / or, the polymerization reaction temperature in step S3 is 20-80°C; And / or, the polymerization reaction time in step S3 is 12-48 h; And / or, the post-processing in step S4 includes one or more processing steps of centrifugation, washing and freeze-drying.
3. The method for preparing polydopamine nanosheets according to claim 2, characterized in that: The phospholipid is one or more of phosphatidylcholine, phosphatidylethanolamine, phosphatidylserine, phosphatidylinositol, phosphatidylglycerol and glycerophosphatidic acid; And / or, the amphiphilic fatty acid is an alkyl acid having 8 to 22 carbon atoms in the carbon chain; And / or, the amphiphilic fatty amine is an alkylamine having 8 to 22 carbon atoms in the carbon chain.
4. The method for preparing polydopamine nanosheets according to claim 2, characterized in that: And / or, the volume ratio of the solvent in step S1 to the deionized water in step S2 is 1:(1-300); And / or, the stirring time in step S2 is 0.1-1 h; And / or, the molar ratio of dopamine in step S3 to the organic substance having self-assembly molecule in step S1 is (2-40):1; And / or, the polymerization reaction temperature in step S3 is 25-60°C; And / or, the centrifugal rotation speed is 5000-20000 rpm and the time is 5-60 min.
5. A polydopamine nanosheet, characterized in that: The polydopamine nanosheet is prepared by the preparation method according to any one of claims 1 to 4, and the size of the polydopamine nanosheet is 0.1-10 μm and the thickness is 0.7-30 nm.
6. A method for preparing a polydopamine-polyester composite material, characterized in that: The following steps are involved: D1. Add the polydopamine nanosheets according to claim 5 into diol, and stir and disperse them evenly to form a dispersed solution; D2. After adding the dibasic acid and / or its esterified product into the dispersed solution in step D1, esterification and / or transesterification and polycondensation reaction are carried out to synthesize the polydopamine-polyester composite material.
7. The method for preparing the polydopamine-polyester composite material according to claim 6, characterized in that: The diol in step D1 includes aliphatic diol and / or cyclic diol; And / or, the stirring speed of the stirring and dispersing in step D1 is 1000-20000 rpm and the time is 0.1-72 h; and / or, the content of polydopamine nanosheets in the dispersed solution in step D1 is 0.01-10 wt %; And / or, the polydopamine nanosheets in step D1 are polydopamine nanosheet powder or polydopamine nanosheet slurry; and / or, the dibasic acid in the dibasic acid and / or its ester in step D2 comprises one or more of terephthalic acid, terephthalic acid esters, furandicarboxylic acid, furandicarboxylic acid esters, thiophenedicarboxylic acid and thiophenedicarboxylic acid esters; And / or, the molar ratio of the dibasic acid and / or its ester in step D2 to the diol in step D1 is 1:(1.2-3).
8. The method for preparing the polydopamine-polyester composite material according to claim 7, characterized in that The aliphatic diol includes one or more of ethylene glycol, propylene glycol, butylene glycol, pentylene glycol, hexylene glycol, octanediol, neopentyl glycol and isosorbide; And / or, the cyclic diol includes one or more of tricyclodecanediol, tricyclodecane dimethanol and tetracyclic diol.
9. A polydopamine-polyester composite material, characterized in that: The polydopamine-polyester composite material is prepared by the preparation method according to any one of claims 6 to 8.
10. Application of the polydopamine-polyester composite material according to claim 9 in the packaging field and the biomedical field.
Citation Information
Patent Citations
Preparation method and adsorption application of polymer nanosheet capable of accurately controlling molecular imprinting process
CN113813933A
Preparation method and application of two-dimensional MXene / polydopamine composite desalination electrode material
CN113881040A
Preparation method and application of amine polymer and transition metal sulfide self-assembled porous nanofiltration membrane
CN115445447A
Modified sheet silicate, its production, polyester resin composition containing same and its production
JP2000086232A
Highly selective ultrathin polymer nanofilm composite membrane and process for preparation thereof
US20230055803A1
Cited By
Sulfur-containing polydopamine melanin nano particle as well as preparation method and application thereof
CN120309944A
